2019
DOI: 10.2136/vzj2019.04.0034
|View full text |Cite
|
Sign up to set email alerts
|

The Texas Soil Observation Network:A Comprehensive Soil Moisture Dataset for Remote Sensing and Land Surface Model Validation

Abstract: Core Ideas TxSON is a Core Cal/Val Site for the NASA SMAP, SMOS, and Sentinel programs. TxSON consists of 40 in situ locations nested within a 36‐km EASE2 grid cell. Locations monitor soil moisture, temperature, and precipitation at 5, 10, 20, and 50 cm. Hourly, quality‐controlled data from 2015 to 2018 are available. The spatiotemporal variability of soil water content (SWC) at the remote sensing scale requires dense monitoring for calibration and validation. Here, we present an overview of the Texas Soil O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…The CS659 water content sensor for HydroSense II (Campbell Scientific) is a 12‐cm electrode version of the CS65x (e.g., CS650/655), and all CS65x are new versions of the original CS615 WCR (Figure 2e; Caldwell, Bongiovanni, Cosh, Halley, & Young, 2018). It is worth noting that all the new CSI TLO are referred to as “CS65x.” The CS65x has been used in various research fields that require ground‐based SWC measurements; for instance, it was used in optimizing satellite‐based SWC data (Bai, He, & Li, 2016), investigating tree establishment conditions (Morrison, Holdo, Rugemalila, Nzunda, & Anderson, 2019), and validating satellite‐ and model‐based SWC data (Caldwell et al., 2018, 2019; Moller, Jovanovic, Garcia, Bugan, & Mazvimavi, 2018). In this study, we used the CS659 with the HydroSense II portable device.…”
Section: Methodsmentioning
confidence: 99%
“…The CS659 water content sensor for HydroSense II (Campbell Scientific) is a 12‐cm electrode version of the CS65x (e.g., CS650/655), and all CS65x are new versions of the original CS615 WCR (Figure 2e; Caldwell, Bongiovanni, Cosh, Halley, & Young, 2018). It is worth noting that all the new CSI TLO are referred to as “CS65x.” The CS65x has been used in various research fields that require ground‐based SWC measurements; for instance, it was used in optimizing satellite‐based SWC data (Bai, He, & Li, 2016), investigating tree establishment conditions (Morrison, Holdo, Rugemalila, Nzunda, & Anderson, 2019), and validating satellite‐ and model‐based SWC data (Caldwell et al., 2018, 2019; Moller, Jovanovic, Garcia, Bugan, & Mazvimavi, 2018). In this study, we used the CS659 with the HydroSense II portable device.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps most importantly, the spacing of the station measurements (number and distribution) must allow a reliable estimation of the average SM over the SMAP footprint. The required minimum number of point-scale sensors and their spacing is dictated by the spatial variability of SM within the area of interest and the desired accuracy for the estimate at that spatial scale (e.g., [64], [65], [66], [67], [68], [9], [10], [69], [70], [71]). For the SMAP CVS, Voronoi diagrams ( [72]; or see Thiessen Polygons in [73]) were chosen as the baseline upscaling approach to avoid geographical overweighting of clustered parts of the pixels [54].…”
Section: Core Validation Sitesmentioning
confidence: 99%
“…Conversely, the time-varying component of SM typically has a large autocorrelation over long distances; that is, point measurements can better represent the SM temporal changes over domains of several km [76], [77]. Many studies of temporal stability of SM very effectively illustrate these differences of spatial and temporal evolution of SM (e.g., [78], [79], [80], [11], [81], [70]). Generally, the sparse networks lack adequate representation for resolving bias and RMSE at the scale of satellite SM retrieval footprints.…”
Section: Core Validation Sitesmentioning
confidence: 99%
“…Detailed descriptions of the areas and experiments have been reported in [69], [71]- [80], and are summarized in TABLE II. These previous studies have demonstrated the spatial representativeness of the in situ networks for the watersheds through intensive field campaigns, thus providing reliable in situ soil moisture observations to validate data products from existing satellite SM missions [11], [14], [16], [46], [74], [81], [82].…”
Section: Data For Evaluation and Comparisonmentioning
confidence: 99%